Acknowledgment of Chimica Techno Acta’s reviewers for 2023 - Dmitry A. Medvedev (Chimica Techno Acta, 2023)
We thank the scientists and experts in various fields represented in Chimica Techno Acta (CTA) for dedicating their time and effort to review the papers that we have sent them. Their assistance ensures that the CTA journal maintains a high-quality peer-review process, which is of paramount importance for the published articles. The CTA editorial office appreciates the contributions of the following reviewers and looks forward to future collaboration.